A Mixed Method study on Pattern and Predictors of Plastic Pollution in an Urban block of West Bengal (Indian Journal of Public Health Research & Development, 2025)
BACKGROUND-   Plastic pollution is one of the gravest environmental concerns of our time, the impact of which have not been studied in detail in our part of the country. Thus an understanding of the distribution and determinants of plastic pollution would be imperative in combating it.AIM- To quantitatively delineate the Knowledge , Practice , Risk Perception and Intention to carry action among households residing in Urban Field Practice Area of All India Institute of Hygiene & Public Health and map the distribution of Macro Plastic Accumulation and qualitatively comprehend the risk perception and prioritization of action among those causing and mitigating plastic pollution.Materials and Methods: This cross-sectional, convergent parallel mixed method study was done among 148 Households & 38 participants for in depth interview, of Urban Health Field Practice area of a public health institute of Kolkata. A pretested questionnaire, observational checklist for spot mapping and an in-depth interview guide was used to collect data. Households were evaluated on 3 categories of knowledge, Risk perception and intention to carry action and bivariate correlation was done, in-depth interview of key-informants was done till data saturation.  Statistical analyses were done in SPSS 16.0.RESULTS - Bivariate correlation was done- the knowledge score and perception score showed weakly positive correlation which is not significant. (Correlation co-efficient -0.159, significance at 2 tail – 0.054). The risk perception score and intention to carry action score showed weakly positive correlation which is significant. (Correlation coefficient- 0.254 and significance at two tail 0.002). The knowledge score and Intention to action score showed weakly positive correlation which is significant (correlation coefficient – 0.217 and significance at 2 tail 0.008). In-depth interview of key participants points to the fact that the extremely severe problem of plastic pollution has already reached disastrous potential and fast running out of control. Lack of cheap and versatile packaging product as plastic and government regulations leads to rampant use of plastic products and its improper disposal.CONCLUSION - Since Knowledge, risk perception and intention to action show positive correlation, Education about plastic pollution through school, mass awareness campaigns, mass media and social media is of utmost importance to combat plastic pollution. Legislature on extent of plastic use and complete ban on single use plastic products along with enough awareness to enforce such laws may go a long way in combating the menace.